Adaptation, translation and validation of the diabetes mellitus in the offspring questionnaire (DMOQ): the Malay version / Siti Fatimah Badlishah Sham - Badlishah Sham, Siti Fatimah (2016)
Offspring of T2DM patients have an increased risk of developing T2DM. One of the approaches to prevent their offspring from developing T2DM is to encourage T2DM patients to become the health promoter within the family. The Diabetes mellitus in the offspring questionnaire (DMOQ) assesses the perceptions of T2DM patients on the risk of their first degree relatives in developing T2DM and the possibility of intervention to reduce this risk. The DMOQ English version consisted of 34-items framed within seven concepts based on the Health Belief Model.